Height adjustment reduces occurrence of low bone mineral density in children and adolescents with HIV - Andrade,Leonardo Bandeira de (2021)
SUMMARY OBJECTIVE: The aim of this study was to quantify the reduction of bone mineral density with and without height adjustment. METHODS: A cross-sectional study was performed with 69 Brazilian children and adolescents vertically infected by HIV. Bone mineral density was measured by dual-energy absorptiometry in the lumbar spine. Anthropometric, demographic, and clinical variables were analyzed. A specific calculator was used for height adjustment. RESULTS: The majority of participants (52.2%) were adolescents and did not present with immunological alterations (61%). Reduced bone mineral density (Z-score <-1) was present in 23.2% and low bone mass (Z-score <-2) in 5.8%. After height adjustment, these occurrences decreased to 11.6% and 0%, respectively. Patients with reduced bone mineral density had a higher mean age and lower body mass index than patients with normal bone mineral density. CONCLUSION: The occurrence of reduced bone mineral density decreased after adjustment for height.